Cartographic representation of highly polluting industries in the city of Baghdad (Journal of the College of Basic Education, 2023)
The industrial concentration within cities and the subsequent huge urban agglomerations have led to pollution of the natural environment in a way that harms human, animal and plant life and threatens their continuity and results in many intractable diseases, foremost of which is cancer.The research was based on the hypothesis (that the presence of large and numerous industries endemic within the city of Baghdad and their industrial waste combined led to the emergence of highly polluted areas) and to show the extent of their danger to the neighboring residential neighborhoods called for this research.The study also assumes that there are (cartographic methods through which the highly polluting industries can be represented in the city of Baghdad).As for the methodology of the study, the research dealt with the following topics:Environmental pollution, degrees of pollution, forms of pollution, determinants of the spatial signature of polluting industries in Iraq, types of highly polluting industries in the city of Baghdad, cartographic representation of the locations of highly polluted industries in Baghdad.